EVALUATING THE ORAL MUCOSA AND NON-CARIOUS DENTAL LESIONS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: A DIAGNOSTIC CHALLENGE (International Conference on Medical Science, Medicine and Public Health, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic systemic condition that predisposes individuals to a variety of oral health problems. This article explores the range of mucosal and non-carious dental lesions observed in patients with T2DM and emphasizes the diagnostic complexity posed by overlapping symptoms and comorbidities. Special focus is given to xerostomia, candidiasis, burning mouth syndrome, wedge-shaped defects, erosions, and hypersensitivity. The paper advocates for improved interdisciplinary care and outlines diagnostic approaches tailored to this patient population.